IMPLEMENTASI KOMUNIKASI MEDIA DALAM TINDAK TUTUR IKLAN PRODUK INDOMIE DI YOUTUBE - Andini Dwi Jayani; Syahminan, Mhd (eScience Humanity Journal, 2023)
Researchers use this research on speech acts to find out how a person's speech conveys a meaning. Researchers use locutionary, illocutionary and perlocutionary speech acts to analyze the problems that exist in instant noodle advertisements on television which are currently very popular with the public. This research is considered important because language is an important object in product marketing. In addition, this research can help expand our knowledge about speech acts in advertising. Here the researcher uses a qualitative descriptive method with pragmatic strategies and advertising analysis which applies a lot of advertising language to Indomie instant noodle products. Researchers obtained this data by observing, listening and recording the content in the advertisement for immediate analysis. The results examined by researchers are about how important it is to use locutionary, illocutionary and perlocutionary speech acts in the world of advertising to express the aims and objectives of making the advertisement.